Characterization of Positive and Suspected COVID-19 Cases with Comorbidities - Yoenny Peña García; Annia Suárez Padilla; Niuva Milagro Arruebarrena Blanco (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Background: factors associated with the severity and worse prognosis in SARS-CoV-2 infection have been described, such as age, the presence of chronic diseases such as diabetes, arterial hypertension and those that compromise the immune system. Objective: to characterize positive and suspected COVID-19 cases with comorbidities in the Puerto Padre municipality between March and May 2020. Methods: a descriptive cross-sectional study was carried out using the information obtained from epidemiological surveys and medical records in the Puerto Padre municipality. The study population was made up of 176 patients. The variables were evaluated: age, sex, symptoms, signs, and comorbidities. For this study, data from epidemiological surveys of the cases detected in epidemiological surveillance and medical records were used. Data were processed using descriptive statistics: calculation of percentages, mean and standard deviation and their confidence interval for 95 % reliability. Results: the mean age was 50 years in suspects and 37 years in confirmed, male sex (53.80 %) prevailed in suspects and female (60.00 %) in positives. The most frequent signs and symptoms in confirmed cases were: fever (28.57 %), cough, nasal congestion and rhinorrhea (14.29 %). In both groups, the most frequent comorbidities were arterial hypertension 119 (69.59 %), smoking 93 (54.39 %), bronchial asthma 46 (26.90 %) and diabetes mellitus 29 (16.96 %). Conclusions: positive and suspected COVID-19 cases with comorbidities were characterized, the most frequent being hypertension, smoking, bronchial asthma, diabetes mellitus, and obesity.